Cultura maker no ensino de química: contribuições para a formação de professores do ensino médio - Lima, Tatiana Rodrigues (2023)
The search for alternatives that can qualify the training of chemistry teachers exists because of the need to improve the methods already rooted in the classrooms, as well as the difficulty of keeping students connected to the school in a world of cultural, technological, and social transformations. The updating of the methodologies and the insertion of new ones in the continuing training of teachers, is characterized by the subject of this work, having as a guiding question: How can maker culture be used to favor the training of chemistry teachers to improve education in secondary school? Anchored in this question, the main objective was to contribute to the training of teachers, from the use of maker culture, thus providing an improvement in the teaching of chemistry. In this line of thought, this research according to its objectives will be of a qualitative character, of action research type, from the interaction of the researchers with the subjects and the situations investigated. Participated in this survey thirteen high school chemistry teachers, linked to one of the Regional Coordinators for Education Development of the northern region of Cear á (Regional Coordinators for Education Development - CREDE). The methodological development took place in two stages, the first being the diagnosis of the profile of the teachers, the organization of the training process and the execution of the workshop. The second stage was the application of the maker workshop, the questionnaire, the interview and the analysis of the results in the light of the literature. The workshop evaluation was carried out through two questionnaires, one before and one after and an interview with a sample of teachers who used the maker method in class, thus generating more input to analyze the impact of the teachers9 workshop. At the end of this work, we will have as an educational product, a digital pedagogical material containing the entire sequence of application of the methodology to allow reproduction and use by other teachers. After carrying out the research and analyzing the data, it was evident in the results that the participating teachers showed that they could use new methods, such as maker culture, as they understood, comprehended and recognized the vast possibilities of this method, at the same time that it allowed them to envision the achievement of high levels of integration and motivation, thus giving meaning to the teaching of chemistry and, consequently, to student learning.